Sustainability in tourist attractions in Malaysia - Hassan, Hamimah; Mahat, Norsyafina; Ali, Mass Hareeza; Abdullah, Nawal Hanim; Abdul Karim, Muhammad Shahrim (American-Eurasian Network for Scientific Information, 2014)
Tourist attraction is a core component in tourism system and the main purpose why visitors travel to a destination. This paper discusses the roles of sustainable development practices in four tourist attractions in Melaka, Malaysia. The main purpose of the research is to examine how does the public and private owned tourist attractions survive over the years, that has led them to sustain and still offering their products to the visitors. Results revealed various strategies that were implemented and these strategies are in line with sustainable tourism concept and also focused strategies with regards to operation management of the tourism sites. The sustainable tourism concept reveals that tourism has the characteristics to improve quality of life of the host community, provide quality experience to the visitors and maintain quality environment for usage of both tourist and the host community. Therefore, a comprehensive dimension in sustainable tourism for managing tourism attractions is proposed.